Pelayanan Kesehatan Reproduksi bagi Narapidana Wanita di Rumah Tahanan Negara Klas I Surakarta - Putri Ratna Kartika Ningrum; Retno Suryawati (Jurnal Kapita Sosial Politik, 2024)
The Surakarta Class I State Detention Center (RUTAN) is a residence for convicts and detainees to spend their sentences. As a residence, the Surakarta Class I State Detention Center (RUTAN) provides services to convicts and detainees, one of which is health services for prisoners and detainees, while in one of the health services there are reproductive health services. The Surakarta Class I State Detention Center (RUTAN) is not only inhabited by men but also women because reproductive health is very important for women, so this research aims to see how accessible reproductive health services are for inmates and detainees at the State Detention Center (RUTAN ) Class I Surakarta. This research aims to determine the accessibility of reproductive health services for prisoners and female detainees at the Surakarta Class I State Detention Center (RUTAN). The results of this research can be concluded that reproductive health services for inmates and detainees at the Surakarta Class I State Detention Center (RUTAN) have not yet met some accessibility, such as the availability of sanitary napkins, pain relievers and information.